1993
DOI: 10.1203/00006450-199309000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α1-Antichymotrypsin and α1-Antitrypsin by Human Trophoblast

Abstract: ABSTRACT. al-Antichymotrypsin (al-ACHY) and al-an-(I). al-AT and aI-ACHY play major roles in the host response titrypsin (al-AT) are closely related glycoprotein protease to trauma and inflammation. The major function of aI-AT, inhibitors, present in plasma and other extracellular fluids, which is present at high levels in human plasma (1 5 3 . 5 mg/ that neutralize proteases released by leukocytes in re-mL), is to inhibit elastases released by leukocytes at sites of sponse to trauma and inflammatory stimuli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
(18 reference statements)
2
20
0
1
Order By: Relevance
“…2) are in agreement with other studies of breast cancer (29 ). One study showed that ␣-1-antichymotrypsin was synthesized by MCR-7 breast cancer cells (30,31 ) and that synthesis was stimulated by epidermal growth factor (32 ) and insulin-like growth factors (33 ), which may protect the tumor from invading leukocytes (34,35 ).…”
Section: Evaluation Of Potential Biomarkers With Disease and Patient supporting
confidence: 88%
“…2) are in agreement with other studies of breast cancer (29 ). One study showed that ␣-1-antichymotrypsin was synthesized by MCR-7 breast cancer cells (30,31 ) and that synthesis was stimulated by epidermal growth factor (32 ) and insulin-like growth factors (33 ), which may protect the tumor from invading leukocytes (34,35 ).…”
Section: Evaluation Of Potential Biomarkers With Disease and Patient supporting
confidence: 88%
“…This results in the proteolytic cleavage of the reactive center peptide bond between Met 358 and Ser 359 of the secreted form of SERPINA-1 40. SERPINA-1 is synthesized by the liver, macrophages neutrophils and also by trophoblast 41. Increases in serum SERPINA-1 occur in diseases such as rheumatoid arthristis, vasculitis, infections and other diseases associated with an inflammatory component 42.…”
Section: Discussionmentioning
confidence: 99%
“…We identified three proteins, ␣-1-antitrypsin, ␣-1-acid glycoprotein, and ␣-1-B glycoprotein. Both ␣-1-antitrypsin and ␣-1-acid glycoprotein are secreted proteins, are produced in the human (13) and rat (14) placenta, respectively, and have been shown previously to bind thyroid hormone at low affinity (15). Little is known of the biological function of the final protein identified, ␣-1-B glycoprotein.…”
Section: Discussionmentioning
confidence: 99%